Qardh Agreement on Spaylater Limit Loans According to The View of MUI Fatwa About Sharia Electronic Money - Hikmatul Komaria (Rechtenstudent, 2023)
SPayLater is a shopping loan provided by Shopee. SPayLater loans can be used by users to buy their needs in installments without a credit card. This SPayLater Limit Loan uses the Qardh contract. A Qardh contract is a loan given by one person to another with the condition that the borrower must return the value of what was borrowed. The issue of this legal research is: what is the mechanism for the SPayLater limit loan at Shopee and what is the Qardh contract for the SPayLater limit loan according to the view of DSN-MUI Fatwa No: 116/DSN-MUI /IX/2017 concerning Sharia Electronic Money. The research method used is an empirical research method with a qualitative approach. Data collection techniques that researchers use are structured interviews, participatory observation and document study. This research obtained results in the form of. 1). The SPayLater feature does not appear in every Shopee user account, only selected Shopee user accounts can register SPayLater. The SPayLater limit loan cannot be disbursed and can only be used for transactions on the Shopee application. 2). The provision of SPayLater limit loans provided by Shopee to its users has fulfilled the principles of the Qardh contract, because the pillars and conditions in the Qardh contract have been fulfilled. Furthermore, according to the view of the DSN-MUI Fatwa regarding Islamic Electronic Money, the Qardh contract provisions are not related. Because the conditions aqidnya not met.